A Review on Recent Developments in Wireless Power Transfer (International Journal of Food and Nutritional Sciences, 2019)
This paper reviews various wireless charging techniques and most recent developments in wireless power transfer. As technology is building up, the usual charging with wires is replaced by wireless charging (WC), so that charging and controlling turns out to be simple and reduction of wires increases the Power Transmission Efficiency (PTE). In this paper various wireless charging methods are reviewed and limitations of each technique are identified (i.e. inductive power transfer and capacitive power transfer). The scope for development in terms of designing of converters and impedance matching networks used in transmitter and receiver sides is highlighted.